Application of Nano-Delivery Systems in Lymph Nodes for Tumor Immunotherapy - Yiming Xia; Shunli Fu; Qingping Ma; Yongjun Liu; Na Zhang (Nano-Micro Letters, 2023)
Highlights The physiological structure and the drug delivery barriers of lymph nodes were described. The factors affecting lymph nodes accumulation in nano-delivery systems were discussed. The recent progress of nano-delivery carriers applied for lymph nodes immunotherapy was further categorized and reviewed.